Transformative art: art as means for long-term neurocognitive change - Preminger, Son (Frontiers in Human Neuroscience, 2012)
Every artwork leads to a unique experience by the observer or participant, may it be sensory, emotional, cognitive, interactive, or spiritual experience. At the neurobiological level, such experiences are manifested as activation of the corresponding neural networks. Neuroscience has demonstrated that experience, in particular repeated experience, can cause a long-term change in the involved brain circuits (experience-dependent plasticity). This review will discuss the molding and transformative aspect of arts, examining how repeated and on-going experience of arts may alter cognitive, emotional, and behavioral patterns as well as their underlying neural circuits. The application of this approach to cognitive training and neuropsychological rehabilitation methods will be addressed as well. In addition, it will be suggested that this approach to art, as a long-term transformative medium, may lead to a novel viewpoint on art and a different approach to its creation. Artists can design artworks that aspire to form, in addition to one-shot influencing experience, on-going experiences which gradually create a lasting change, possibly improving audiences' neuropsychological functions.